2023
DOI: 10.3389/fpubh.2022.991828
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of leprosy during the period 2005–2020: A retrospective study based on the Chinese surveillance system

Abstract: BackgroundJiangsu Province is located in the Yangtze River Delta region, with a total area of 107,200 square kilometers. Since 1949, over 55,000 cases have been registered, with Taixing accounting for the highest number of patients. The proportion of new cases with MB and G2D was higher compared to other regions. As a result, Jiangsu has been considered a priority area for public health interventions in China.MethodsThis paper mainly described the population, time, and spatial distribution of the newly detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
2
4
0
1
Order By: Relevance
“…Improvements in treatment explain the decrease in most symptoms over the periods, while a greater awareness and responsibility for health among individuals is linked to other location of symptoms. Similar studies found that skin symptoms on the limbs are the most common [27,38,50].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Improvements in treatment explain the decrease in most symptoms over the periods, while a greater awareness and responsibility for health among individuals is linked to other location of symptoms. Similar studies found that skin symptoms on the limbs are the most common [27,38,50].…”
Section: Discussionsupporting
confidence: 63%
“…The male predominance is also mentioned by other authors [25,[27][28][29][30][31][32][33][34][35]. This male predominance could be related to the under-diagnosis of women: their physical examination was less thorough due to cultural customs and limited access to health services [2,31].…”
Section: Discussionmentioning
confidence: 69%
“…The Jiangsu Province used to have one of the most considerable rates in China, with a total of 56,176 leprosy cases detected and registered from 1949 to 2020. A previous study [8] showed that, during the period of 2005-2020, there was a 31.68% of newly discovered G2D patients and it was significantly higher than in other endemic areas of China, such as Yunnan, Sichuan, and Guizhou. However, leprosy burden is often misinterpreted as the eradication or the absence of major complications in Jiangsu.…”
Section: Introductionmentioning
confidence: 87%
“…WHO telah menargetkan eliminasi kusta sebagai tujuan kesehatan masyarakat untuk mengurangi insiden global menjadi <1/100.000 pada tahun 2000, dan sebagian besar negara telah mencapai tujuan tersebut (5). Namun, kusta terus tercatat di lebih dari 120 negara, dengan 200.000 kasus baru dilaporkan setiap tahunnya.…”
Section: Pendahuluanunclassified